Metal-3D-printed permeable leading edges for airfoil noise reduction - Ocker, Christof; Geyer, Thomas F.; Czwielong, Felix; Becker, Stefan; Merkel, Markus (Quality Analysis of Additively Manufactured Metals, 2022)
Additive manufacturing offers many possibilities compared to conventional manufacturing methods, which makes it a very promising tool for industry sections like aerospace or energy due to the high accuracy, structural stability, and the possibility to integrate additional functionalities into complex parts and assemblies. One example includes the rotor and/or stator blades of turbomachinery, which can be modified in order to reduce the generation of aerodynamic noise using permeable, Metal-3D-printed structures integrated into the blade leading edge. An experimental study of the aerodynamic and the aeroacoustic performance of airfoils with additive manufactured permeable leading edges under disturbed inflow conditions is presented. A turbulent inflow increases the noise emission of the airfoils, which is related to turbulence interaction noise. By integrating a permeable structure on the leading edge of the airfoils, the noise emission can be reduced. However, these modifications may reduce the aerodynamic performance of the airfoil. For the identification of quiet and aerodynamically effective leading-edge modifications, high dimensional accuracy of the geometrically thin structures is required. Therefore, the geometry of the manufactured airfoils with integrated leading-edge modification was measured with computer tomography and compared to the computer-aided design model. Then, wind tunnel measurements were conducted to identify the aerodynamic and aeroacoustic performance of the airfoils.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Airfoil; Dimensional accuracy; Noise reduction; Permeable leading edge